Visible light driven, nickel-catalyzed aryl esterification using a triplet photosensitiser thioxanthen-9-one. Issue 14 (21st May 2019) - Zhu, Da-Liang; Li, Hong-Xi; Xu, Ze-Ming; Li, Hai-Yan; Young, David J.; Lang, Jian-Ping
Abstract : The nickel-catalyzed esterification of carboxylic acids with aryl bromides using thioxanthen-9-one as a photosensitizer provided aryl esters with excellent yields. Abstract : We report an approach to the visible light-initiated, nickel-catalyzed esterification of carboxylic acids with aryl bromides. Thioxanthen-9-one works as a triplet photosensitizer to significantly accelerate this cross-coupling to provide aryl esters in moderate to excellent yields at room temperature. A mechanistic investigation indicates that this esterification undergoes the stepwise oxidative addition of an arylbromide to nickel, transmetalation of an aryl–Ni(ii ) bromide complex, energy transfer from thioxanthen-9-one to an excited-state aryl–Ni(ii ) carboxylate and reductive elimination to the aryl ester. This study contributes to the utilization of ketones as triplet photosensitisers in photochemical transformations.